HUBUNGAN KOMPETENSI PROJECT MANAGER TERHADAP KEBERHASILAN PROYEK KONSTRUKSI GEDUNG - Ida Ayu Ari Brahmantariguna; GAP. Candra Dharmayanti; I W. Yansen (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract :One of the factor that influences the achievement of a project success is the role of a project manager. A reliable project manager, who knows his duties as a project leader and has the necessary competency requirements is needed to achieve the success of the project. The competence of a project manager can be measured by three aspects: knowledge, skill and attitude.This research aims to analyze the relationship between project manager competencies (that measured by three independent variables, i.e. Knowledge, skills and attitude) and the success of the building construction project. Data was collected through a questionnaire survey. The sample/ respondents were the expertise in the field of building construction services those acts as a project manager. Data was analyzed in three stages:first, factor analysis to reduce the variables into several groups of factors, that called as independent variables; second, correlation test with Pearson Correlation method to determine the correlation between independent variables and dependent variable; lastly, perform multivariate regression analysis The results of factor analysis showed that the variables are formed into eleven groups, and the result of Pearson Correlation test showed only six groups correlated to project success, those are: Communication and Scope Management, Human Resource Management, which is part of knowledge; Leadership and Project Management, Professionalism and Issues Management as part of skill; and attitude concerning Responsibility, Vision and Priorities. The sixth group of these factors will be the independent variables in multivariate regression analysis. Based on multiple correlation test results, six independent variables simultaneously have a significant influence to the project success, proved by the result of probability value is 0,032.